"Moderate" Arab States: From the Cold War to the Syrian Conflict. Issue 1 (6th June 2021) - Voller, Yaniv
Abstract: Moderation has been a recurring theme in international politics, particularly in the international politics of the Middle East, where foreign and regional actors have often categorized others and themselves as either "moderates" or "radicals." However, very few works have sought to deconstruct the meaning of moderation in this context. Those that have addressed the issue have mostly treated moderation as a Western attempt to simplify regional geopolitics and dichotomize the actors to justify their choices of allies and foreign policy toward the region. This article argues that "moderate" has evolved from a category of analysis to one of practice. The so‐called moderates, after negotiating the word's meaning, have embraced it as a description of themselves. Through an examination of the evolution of the "moderate" Arabs label from the Cold War to the Syrian civil war, the article demonstrates that the word has evolved through negotiations among the foreign powers that introduced it and the so‐called moderates themselves. Furthermore, it demonstrates the role that the label as a category of practice has come to play in regional geopolitics.